Evaluating rural sports tourism competitiveness: A framework applied to Shandong province - Lijun Yin; Qian Gu; Xueting Gao; Pengfei Tai; Li Cao (PLoS ONE, 2025)
Rural sports tourism performs a crucial role in developing the rural sports industry and promoting rural revitalization. We investigate the competitiveness of rural sports tourism in Shandong Province through niche theory, developing a five-tier index system in the context of resource base, industrial development, location conditions, fundamental guarantees, and construction management. A least squares optimization model is used to identify both subjective and objective weights for the indicators. In detail, we evaluate the niche intensity and overlap of 16 cities, suggesting significant disparities in competitiveness. Higher niche overlap correlates with enhanced competition, emphasizing the need for better resource development, diversified economic formats, as well as stronger location conditions, basic guarantees, marketing management, and city-level cooperation. These findings not only offer practical recommendations for enhancing competitiveness, but also provide theoretical guidance for the high-quality development of regional rural sports tourism.